2007
DOI: 10.1162/jocn.2007.19.6.1050
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Processing without Semantics? An Event-related Brain Potential Study of Preschoolers using Jabberwocky Sentences

Abstract: Abstract& Behavioral studies have demonstrated that children develop a nearly adult-like grammar between 36 and 42 months, but few studies have addressed how the child's brain processes semantic versus syntactic information. In previous research, Silva-Pereyra and colleagues showed that distinct event-related potentials (ERPs) are elicited by semantic and syntactic violations in sentences in children as young as 30, 36, and 48 months, following the patterns displayed by adults. In the current study, we examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
1
7
0
2
Order By: Relevance
“…By 11 months of age, phonetic learning can already be observed; by 14 months, responses to known words are observed; and by 2.5 years, semantic and syntactic learning is elicited (Kuhl and Rivera-Gaxiola, 2008). For instance, a P600 to sentence-level syntactic violations has been found in 30, 36, and 48 months old children that looked rather similar to the P600 found in young adults (Silva-Pereyra et al, 2007). …”
Section: Exploring Sequential Learning With Event-related Potentialssupporting
confidence: 54%
“…By 11 months of age, phonetic learning can already be observed; by 14 months, responses to known words are observed; and by 2.5 years, semantic and syntactic learning is elicited (Kuhl and Rivera-Gaxiola, 2008). For instance, a P600 to sentence-level syntactic violations has been found in 30, 36, and 48 months old children that looked rather similar to the P600 found in young adults (Silva-Pereyra et al, 2007). …”
Section: Exploring Sequential Learning With Event-related Potentialssupporting
confidence: 54%
“…At least in human adults, this late positivity may involve or be related to the P3a, an ERP component seen with oddball paradigms414445. As a point of reference, late ERP components for syntactic processes do not seem to appear in children until the age of 2.5 to 3 years4647. In the nonhuman primates, the late positive ERP component that we label as a LP could be related to the reported P500 in macaques that responds to adjacent sequencing relationships38.…”
Section: Discussionmentioning
confidence: 70%
“…It has been argued that the word-word associations that make up the class of color words are learned from how frequently those words are heard together in speech, and that these associations can bootstrap into the more specific word-color mapping that emerge later on (Sandhofer & Smith, 1999). Lastly, in an EEG study, 3-year-olds showed signatures of semantic processing when they heard sentences comprising novel content words and familiar function words (Silva-Pereya, Conboy, Klarman & Kuhl, 2007). This finding supports the interpretation that toddlers in the current experiment are extracting meaning from the training sentences, despite the presence of novel words.…”
Section: Discussionmentioning
confidence: 99%